Inclusive Education National Research Advocacy Agenda: A Call to Action. (September 2016) - Morningstar, Mary E.; Allcock, Heather C.; White, Julia M.; Taub, Deborah; Kurth, Jennifer A.; Gonsier-Gerdin, Jean; Ryndak, Diane L.; Sauer, Janet; Jorgensen, Cheryl M.
The TASH Inclusive Education National Committee responded to Horner and Dunlap's call to ensure that future research integrates inclusive values with strong science by developing an inclusive education national research advocacy agenda. Qualitative methods were implemented to answer three questions: (a) What is the state of inclusive education research? (b) What research still must be done? and (c) What are recommendations for a national inclusive education research advocacy agenda ? The findings include 15 areas organized within three domains advocating for continued research across systems-level capacity building, building and classroom capacity, and student learning and development. Implications for research and policy reform are discussed.